Home away from home? Boarding in Australian schools. (April 2013) - Hodges, Julie; Sheffield, Jeanie; Ralph, Alan
Currently, Australian boarding schools undertake to provide a home away from home for around 20, 000 adolescents. Research documenting the boarding school experience is scarce, and, with few exceptions, exists as a less significant aspect of more general research into private school education. Such school-based research focuses on the positive, character-building benefits of the boarding experience. However, case studies of former boarders paint quite a different picture. In order for boarding schools to best support boarders' development, it is vital that adults who fulfil a parenting role undertake appropriate training. This paper draws together available information to present a comprehensive picture of boarding in Australian schools, with a focus on the challenges faced by the in loco parentis role of staff. It is apparent that more skills-based training is vital to better equip staff in this very important role.